PENINGKATAN KEMAMPUAN GURU BAHASA INDONESIA DALAM MENYUSUN RENCANA PROGRAM PEMBELAJARAN (RPP) SDN 015 PAGARAN TAPAH DARUSSALAM MELALUI METODE PEMBERIAN TUGAS - ', Mukhlis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the observation of some teachers found the symptoms as follows: the lack of abilityof Indonesian teachers in designing learning program (RPP), the learning device is only usedas a supplement and not to the needs of teaching, most teachers again if asked the lessonanswered not have or has not been made. The purpose of this research is to improve theability of Indonesian teachers in designing learning program (RPP) at SDN 015 PagaranTapah Darussalam through the method of administration tasks. This type of research is actionresearch school. Subjects in this study were teachers Indonesian as many as 12 people. Basedon the analysis and discussion can be concluded that the method of administration tasks canimprove the ability of Indonesian teachers in making learning device in SDN 015 PagaranTapah Darussalam through the method of administration tasks. Under these conditions, thelevel of acceptance of teachers increased. The aspect ratio capability Indonesian teachers inpreparing lesson plans through the provision of duty cycle I and II of the increase from 56%and the second cycle to 79%.